'It's being a part of a grand tradition, a grand counter-culture which involves communities': A qualitative investigation of autistic community connectedness. (November 2022) - Botha, Monique; Dibb, Bridget; Frost, David M
Autistic people report greater comfort socialising and easier communication with each other. Despite autism being stereotypically associated with lack of social motivation, an autistic community has been described briefly in the literature but is not well understood. Autistic community connectedness may play a role in promoting wellbeing for autistic people. This qualitative study involved interviewing autistic individuals ( N  = 20) in-person, via a video-based platform, a text-based platform or over email to investigate autistic community connectedness. Critical grounded theory tools were used to collect and analyse the data. There were three elements of autistic community connectedness: belongingness, social connectedness and political connectedness. Belongingness referred to the sense of similarity that autistic people experienced with each other. Social connectedness referred to specific friendship participants formed with other autistic people. Political connectedness referred to a connectedness to the political or social equality goals of the autistic community. Participants described the benefits of autistic community connectedness as being increased self-esteem, a sense of direction and a sense of community not experienced elsewhere. Lack of connectedness involved ambivalence with an autistic identity and/or feelings of internalised stigma. Experiences of autistic community connectedness may have implications for autistic people's wellbeing, as well as how they cope with minority stress. Lay abstract: A sense of being connected to other autistic people has been reported anecdotally. Friendships and connectedness may be important to autistic people and beneficial for their wellbeing. Our research aimed to understand the autistic community by interviewing 20 autistic people about their experiences of being connected to other autistic people. Participants were interviewed in person, over video, using a text-based software to type or over email. Participants detailed three parts of autistic community connectedness: a sense of belonging, social connection with autistic friends and political connectedness. The friendships autistic people had with one another were deemed to be very important to participants because it gave them confidence, provided companionship and made them happy. Some participants did not experience connectedness to the autistic community. These participants also found autism to be less important to their identity and had fewer positive feelings about being autistic. This research is important as it raises awareness that community connectedness is viewed as important to this group. It is possible that community connectedness may help protect the mental health of autistic people when they face stigma or negative life experiences in society.